Current Trends in the Optical Characterization of Two-Dimensional Carbon Nanomaterials - Kröner, Anton; Hirsch, Thomas (Frontiers in Chemistry, 2020)
Graphene (and graphene related materials) received great attention because of their outstanding properties like Young’s modulus, chemical inertness, high electrical and thermal conductivity, or large mobility. To utilize 2D materials in any practical application an excellent characterization of the nanomaterials is needed, as in such dimensions even small variations in size or composition are accompanied by drastic changes in material properties. Simultaneously it is sophisticated to perform characterizations at such small dimensions. This review highlights the wide range of different characterization methods for 2D materials mainly attributing carbon-based materials as they are by far the most often used ones today. The strengths as well as limitations of the individual methods ranging from light microscopy (LM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM), scanning tunneling microscopy (STM), (conductive) atomic force microscopy ((c)AFM), scanning electrochemical microscopy (SECM), Raman-, UV-Vis- (UV-Vis), X-ray photoelectron spectroscopy (XPS), X-ray fluorescence spectroscopy (XRF), energy-dispersive X-ray spectroscopy (EDX), Auger electron spectroscopy (AES), electron energy loss spectroscopy (EELS), x-ray diffraction (XRD), inductively coupled plasma atomic emission spectroscopy (ICP OES), to dynamic light scattering (DLS), are discussed. By using these methods, the flake size and shape, number of layers, conductivity, morphology, number and type of defects, chemical composition, and colloidal properties of 2D materials can be investigated.